A State-Level Review of Diversity Initiatives in Congregate Meal Programs Established Under the Older Americans Act. (October 2015) - Porter, Kristen E.; Cahill, Sean
The Older Americans Act (OAA) congregate meal program (CMP) targets those most at risk for nutritional deficiencies, social isolation, and institutionalization. Social minorities (racial, ethnic, cultural, and sexual minorities) are at high risk for all three. This study explores state-level diversity initiatives to welcome these social minorities in CMPs. A national survey was distributed to each State Unit on Aging, all but three states participated. The majority of states (64.6%) target CMPs to a specific racial, ethnic, or cultural minority; five states target sexual minorities (lesbian, gay, bisexual, and transgender [LGBT]). Negative binomial regression results find state minority population percentage is a significant predictor of the number of diversity initiatives at CMPs. States with LGBT CMPs reported the highest levels of racial/ethnic/cultural diversity initiatives and high levels of statewide LGBT protective policies. Recommendations are suggested that build upon the diversification success of states to further the mission of OAA in reaching high-risk older adults.